Copper Redox Cycling Inhibits Aβ Fibre Formation and Promotes Fibre Fragmentation, while Generating a Dityrosine Aβ Dimer. Issue 1 (December 2018) - Gu, Miao; Bode, David; Viles, John
Abstract Oxidative stress and the formation of plaques which contain amyloid-β (Aβ) peptides are two key hallmarks of Alzheimer's disease (AD). Dityrosine is found in the plaques of AD patients and Aβ dimers have been linked to neurotoxicity. Here we investigate the formation of Aβ dityrosine dimers promoted by Cu2+/+ Fenton reactions. Using fluorescence measurements and UV absorbance, we show that dityrosine can be formed aerobically when Aβ is incubated with Cu2+ and hydrogen-peroxide, or in a Cu2+ and ascorbate redox mixture. The dityrosine cross-linking can occur for both monomeric and fibrillar forms of Aβ. We show that oxidative modification of Aβ impedes the ability for Aβ monomer to form fibres, as indicated by the amyloid specific dye Thioflavin T (ThT). Transmission electron microscopy (TEM) indicates the limited amyloid assemblies that form have a marked reduction in fibre length for Aβ(1–40). Importantly, the addition of Cu2+ and a reductant to preformed Aβ(1–40) fibers causes their widespread fragmentation, reducing median fibre lengths from 800 nm to 150 nm upon oxidation. The processes of covalent cross-linking of Aβ fibres, dimer formation, and fibre fragmentation within plaques are likely to have a significant impact on Aβ clearance and neurotoxicity.